ENCORE QUELQUES DÉLOCUTIFS - Ilari, Rodolfo (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
In this article, I review the concept of delocutive derivation, conceived for the first time by Benveniste, who exemplified it prototypically through the Latin verb salutare (to greet) as a derivation from the noun salus (health). I advocate that it might be interesting not to limit this concept to verb derivation and that an enlarged concept of the delocutive process may be useful to explain many derivations in ancient and modern Portuguese. In addition I present some of the problems that the understanding of the delocutive process may bring to a semantics that wishes to consider only the meaning and the reference of linguistic expressions.